Situation aware intelligent reasoning during disaster situation in smart cities - Saleem, Kiran; Akhtar, Salwa Muhammad; Nazir, Makia; Almadhor, Ahmad S.; Zikria, Yousaf Bin; Ahmad, Rana Zeeshan; Kim, Sung Won (Frontiers in Psychology, 2022)
Investigating prior methodologies, it has come to our knowledge that in smart cities, a disaster management system needs an autonomous reasoning mechanism to efficiently enhance the situation awareness of disaster sites and reduce its after-effects. Disasters are unavoidable events, that occur at anytime and anywhere. Timely response to hazardous situations can save countless lives. Therefore, this paper introduces a multi-agent system with a situation-awareness method utilizing NB-IoT, industrial internet of things (IIOT), and edge intelligence to have efficient energy, optimistic planning, range flexibility, and handle the situation promptly. We introduce the belief-desire–intention (BDI) reasoning mechanism in a multi-agent system to enhance the ability to have disaster information when an event occurs and perform an intelligent reasoning mechanism to act efficiently in a dynamic environment. Moreover, we illustrate the framework using a case study to determine the working of the proposed system. We develop ontology and a prototypal model to demonstrate the scalability of our proposed system.